2017
DOI: 10.1111/nph.14876
|View full text |Cite
|
Sign up to set email alerts
|

Source and sink mechanisms of nitrogen transport and use

Abstract: Contents Summary35I.Introduction35II.Nitrogen acquisition and assimilation36III.Root‐to‐shoot transport of nitrogen38IV.Nitrogen storage pools in vegetative tissues39V.Nitrogen transport from source leaf to sink40VI.Nitrogen import into sinks42VII.Relationship between source and sink nitrogen transport processes and metabolism43VIII.Regulation of nitrogen transport43IX.Strategies for crop improvement44X.Conclusions46Acknowledgements47References47 Summary Nitrogen is an essential nutrient for plant growth. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
389
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(403 citation statements)
references
References 284 publications
8
389
0
6
Order By: Relevance
“…The hydroponic experiment showed that the root morphologies of the two B. napus genotypes were affected differently: D4‐15 had more root tips and larger root surface area than D2‐1 under N deficient conditions (Figure S1), suggesting that greater plasticity of the root system might contribute to enhanced NupE and NUE in B. napus (Qin et al, ). Besides changes in root architecture, which affects NupE and NutE, such as N assimilation, remobilization of plant N from senescent to newly growing tissues, and alteration of carbohydrate partitioning might also contribute to NUE (Han, Okamoto, Beatty, Rothstein, & Good, ; Tegeder & Masclaux‐Daubresse, ). NR and GS are two of the most important enzymes in N assimilation (Tegeder & Masclaux‐Daubresse, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroponic experiment showed that the root morphologies of the two B. napus genotypes were affected differently: D4‐15 had more root tips and larger root surface area than D2‐1 under N deficient conditions (Figure S1), suggesting that greater plasticity of the root system might contribute to enhanced NupE and NUE in B. napus (Qin et al, ). Besides changes in root architecture, which affects NupE and NutE, such as N assimilation, remobilization of plant N from senescent to newly growing tissues, and alteration of carbohydrate partitioning might also contribute to NUE (Han, Okamoto, Beatty, Rothstein, & Good, ; Tegeder & Masclaux‐Daubresse, ). NR and GS are two of the most important enzymes in N assimilation (Tegeder & Masclaux‐Daubresse, ).…”
Section: Discussionmentioning
confidence: 99%
“…N uptake capacity, which is determined by influx transporters located on the plasma membranes of root cells, is one of the major determinants of the NupE, in conjunction with an appropriate root architecture that responds to local and systemic N signals (O'Brien et al, 2016;Qin et al, 2019;White, George, Dupuy, et al, 2013). Following uptake by root cells, some nitrate is assimilated within the roots, whilst a larger proportion is translocated to the shoot, where it is first reduced to nitrite by nitrate reductase (NR) in the cytoplasm, then to ammonium by nitrite reductase (NiR) in the plastids, which is metabolized to glutamate (Glu) and glutamine (Gln) by Gln synthetase (GS) and Glu synthase (GOGAT), respectively (Tegeder & Masclaux-Daubresse, 2018;Xu et al, 2012). N assimilation requires both energy and organic carbon (C) which, in the illuminated leaf, are provided by photosynthesis (Nunes-Nesi, Fernie, & Stitt, 2010;Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plants are able to react to these variations thanks to specific NO 3 sensing systems, making this ion one of the most potent signal molecule affecting plant physiology and development [1]. The biochemical mechanisms involved in NO 3 uptake, assimilation and remobilization have been widely studied in order to identify the features that determine the nitrogen use efficiency (NUE) of a plant [2][3][4][5][6]. The effect of low N availability on plant biomass, NO 3 uptake, ion contents and root architecture has been widely investigated [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Both the efficiency of nutrient acquisition and the efficiency of nutrient utilisation are important for breeders (Santa‐Maria, Moriconi, & Oliferuk, ), such that sink development in addition to source strength is vital for realising improved crop productivity (Burnett et al., ; White et al., ). Regarding the key mineral nutrient nitrogen, nitrogen transporters have been identified as a key target for improving the nitrogen source:sink balance (Tegeder & Masclaux‐Daubresse, ), whilst nitrogen allocation patterns are important for nitrogen use efficiency and yield (Perchlik & Tegeder, ). Additional nutrient storage, in order to build up nutrient reserves for subsequent grain filling, would require larger nutrient sinks—such as increased capacity for expansion growth—to develop during the vegetative growth stage.…”
Section: Discussionmentioning
confidence: 99%